STAPEDIAL REFLEX IN PARKINSON'S DISEASE - YOKOKAWA, Tomohisa (Journal of The Showa Medical Association, 1997)
By means of impedance audiometry, the stapedial reflex was recorded and analyzed in 10 patients with Parkinson's disease to determine whether the reflex shows changes. Eight young and eight elderly normal subjects were also as controls. Impedance changes were recorded on an X-Y plotter by contralateral sound stimulation. Sounds applied were 500Hz and 1000Hz, 10dB above the threshold of the reflex, for 1.5 seconds. Four latencies in the reflex curve were evaluated in normal subjects and in patients with Parkinson's disease. There were no significant differences in the latencies between young and elderly normal subjects. However, one of the four latencies (D50) was significantly longer in patients with Parkinson's disease than in the elderly normal subjects. We hypothesize that disturbance of the extrapyramidal system causes prolongation of the latency of the stapedial reflex in patients with Parkinson's disease.